Electrocatalytic contributions from Brazilian research groups for clean energy conversion and environmental remediation - Medina, Marina [UNESP]; Carvalho, Vinícius José [UNESP]; da Silva, Leanderson Araujo [UNESP]; Borges, Gabriel Gonçalves [UNESP]; Capelupi, Thiago [UNESP]; Piani, Arthur [UNESP]; Mauriz, Pedro Paes [UNESP]; Gomes, João Vitor [UNESP]; de Brito, Juliana Ferreira [UNESP] (Springer Nature, 2025)
Our energy generation and other industrial processes on which our current lifestyle is based cause significant environmental impacts. Some widely employed industrial processes are major contributors to CO2 emissions. A prime example is ammonia production, which represents a high energy consumption, utilizes natural gas, and generates hundreds of millions of tons of CO2 annually. Proper waste treatment, alternatives to fossil fuels, and chemical compound production processes are crucial to address these issues. In this regard, (photo)electrochemical techniques such as electrocatalysis (EC) and photoelectrocatalysis (PEC) can aid in the clean and cost-effective treatment of wastewater while also generating new fuels and commercially valuable chemical compounds. Reduction reactions can be specifically applied to (i) CO2 molecules, producing fuels; (ii) N2 molecules, generating NH3; and (iii) H + species, producing H2. Oxidation reactions can be employed for organic and inorganic molecules present in real effluents, aiming to treat contaminated water. Electrocatalytic Brazilian research groups have been contributing not only to those redox reaction investigations but also to the synthesis of electrocatalysts for both reactions, making them more cost-effective, specific, and efficient, opening new perspectives in the generation of environmentally friendly chemical compounds with added value, clean energy conversion (non-petroleum energy), and minimizing the economic impact of environmental wastewater treatments. Thus, this work offers for the first time insights into the strengths, challenges, and prospects of electrochemical applications in the fields of energy and environmental remediation in Brazil, highlighting the country’s significance as a source of scientific knowledge on a global scale.
Keywords: CO2 reduction; Energy conversion; H2 evolution reaction; N2 reduction; Photoelectrosynthesis; Wastewater treatment